Framework-substituted cerium MCM-22 zeolite and its interlayer expanded derivative MWW-IEZ. Issue 8 (15th March 2016) - Roth, Wieslaw J.; Gil, Barbara; Makowski, Wacław; Sławek, Andrzej; Korzeniowska, Aleksandra; Grzybek, Justyna; Siwek, Michał; Michorczyk, Piotr
Abstract : Framework-substituted MCM-22 with up to 5% Ce was prepared by a conventional non-TEOS-based method. Abstract : Framework-substituted cerium MCM-22 zeolites were synthesized with both TEOS and solid silica sources. The Si/Al ratio in the gel was 15/1 with two different Si/Ce ratios equal to 100/1 and 30/1. The products showed high Brønsted acid site concentrations, above 700 μmol g −1, that diminished slightly as the Ce content increased. The state of Ce was evaluated by IR and UV-vis spectroscopy. There was no indication of a separate Ce phase and extraframework atoms. Both oxidation states, 3+ and 4+, were present. In contrast to the interlayer expanded form MCM-22-IEZ with Ce exchanged into it, the present MCM-22 did not show oxidation of adsorbed CO. This indicates fundamental differences in the location of Ce, which is outside the framework in the exchanged form. The framework-substituted Ce-MCM-22 became active for CO oxidation after its conversion into the IEZ form and additional exchange of Ce. Textural properties were evaluated by nitrogen adsorption and quasi-equilibrated temperature-programmed desorption and adsorption (QE-TPDA) of hydrocarbons.